Extending the conceptualisation of class across field and city: Transgressing servitude towards an emancipatory praxis - Thomaz Junior, Antonio [UNESP]; Garvey, Brian (SAGE Publications, 2022)
This article advocates the transgression of incumbent theoretical divisions between rural and urban abodes of production and draws on new analyses of contemporary spaces of capital and labour antagonisms in Brazil. It does so to articulate a broadening of the definition of class and class struggle towards an emancipatory praxis that does not necessarily prioritise industrialised workers. The study has a particular focus on the reconfiguration of socio-spatial arrangements linked to 21st century commodity cultivation, extraction and trade and subsequent class tensions on the material and epistemological frontier between (hydro, agro and mineral) mega projects and the autonomous territories of rural subjects. The renewed degradation of conditions for a labour force that has always been precarious, the dissolving dichotomy between proletarianised and peasant labour, and the ongoing resistance to corporate capture by communities is evoked to contrast distinct metabolic relations within rural territories with the objectification of labour and nature under capitalism. The analysis reveals new configurations of class domination, tension and counter movements. Many critical scholars, particularly those in the Global South, have been attentive to alternate readings of the world by indigenous, African descendent, peasant and agro-extractivist communities that may be unfamiliar yet underpin vociferous, and often fatal, resistance to capital accumulation. The task to effectively situate these struggles within a theory of broader, heterogeneous class struggle and integrate this ‘wealth’ of collective struggle and knowledge towards societal transformation remains important work in progress. In this spirit, the paper offers some possibilities for making new conceptual and material connections between rural and urban productive spaces and across currently fragmented class formations and identities.
Keywords: agrarian; Brazil; labour; praxis; territory